(untitled) (Orinoquia, 2014)
The echoes after the controversy that strikes up the attempt of the national government to cut-off the resources for science budgeted for 2015 has not ceased. The tension led to the resignation of the Colciencias Director. CONPES announces that the investment in science and technology will remain stable with 379.000 million Pesos for 2015. Nevertheless beyond the budgetary problems, Colciencias, the flagship of science, technology and innovation drags into its hull - That barely keeps overwater- a series of problems that keep it from proper navigation Colciencias’ crossroads goes beyond the instability of its head: there are other obvious issues besides the impossibility of increasing its budget in the recent years: